First-in-human phase I trial of the bispecific CD47 inhibitor and CD40 agonist Fc-fusion protein, SL-172154 in patients with platinum-resistant ovarian cancer - Lini Pandite; Simon Metenou; Debra L Richardson; Erika Hamilton; Linda Van Le; Bo Ma; Fatima Rangwala; Nehal J Lakhani; Justin Call; Daphne Stewart; Lauren E Dockery; Guanfang Wang; et al. (Journal for ImmunoTherapy of Cancer)
Background SL-172154 is a hexameric fusion protein adjoining the extracellular domain of SIRPα to the extracellular domain of CD40L via an inert IgG4-derived Fc domain. In preclinical studies, a murine equivalent SIRPα-Fc-CD40L fusion protein provided superior antitumor immunity in comparison to CD47- and CD40-targeted antibodies. A first-in-human phase I trial of SL-172154 was conducted in patients with platinum-resistant ovarian cancer.Methods SL-172154 was administered intravenously at 0.1, 0.3, 1.0, 3.0, and 10.0 mg/kg. Dose escalation followed a modified toxicity probability interval-2 design. Objectives included evaluation of safety, dose-limiting toxicity, recommended phase II dose, pharmacokinetic (PK) and pharmacodynamic (PD) parameters, and antitumor activity.Results 27 patients (median age 66 years (range, 33–85); median of 4 prior systemic therapies (range, 2–9)) with ovarian (70%), fallopian tube (15%), or primary peritoneal (15%) cancer received SL-172154. Treatment-emergent adverse events (TEAEs) were reported for 27 patients (100%), with 24 (88.9%) having a drug-related TEAE and infusion-related reactions being the most common. 12 patients (44.4%) had grade 3/4 TEAEs, and half of these patients (22.2%) had a drug-related grade 3/4 TEAE. There were no fatal adverse events, and no TEAEs led to drug discontinuation. SL-172154 Cmax and area under the curve increased with dose with greater than proportional exposure noted at 3.0 and 10.0 mg/kg. CD47 and CD40 target engagement on CD4+ T cells and B cells, respectively, approached 100% by 3.0 mg/kg. Dose-dependent responses in multiple cytokines (eg, interleukin 12 (IL-12), IP-10) approached a plateau at ≥3.0 mg/kg. Paired tumor biopsies demonstrated a shift in macrophages from an M2- to an M1-dominant phenotype and increased infiltration of CD8 T cells. PK/PD modeling showed near maximal margination of B cells and a dose-dependent production of IL-12 nearing a plateau at >3.0 mg/kg. The best response was stable disease in 6/27 (22%) patients.Conclusions SL-172154 was tolerable as monotherapy and induced, dose-dependent, and cyclical immune cell activation, increases in multiple serum cytokines, and trafficking of CD40-positive B cells and monocytes following each infusion. The safety, PK, and PD activity support 3.0 mg/kg as a safe and pharmacologically active dose.Trial registration number NCT04406623.